STRATEGIC FEASIBILITY OF FGD GYPSUM COMMERCIALIZATION IN A COAL-FIRED POWER PLANT: A CASE STUDY OF PT SUMATERA PEMBANGKIT - Ferandi Eka Yarsi; Atik Aprianingsih (Journal of Economic, Bussines and Accounting (COSTING), 2025)
PT Sumatera Pembangkit, operator of a 1,320 MW mine-mouth coal-fired power plant (CFPP) in South Sumatra, is currently facing increasing challenges in managing its Flue Gas Desulfurization (FGD) gypsum waste, which remains classified as hazardous (B3) material. This by-product remains unused despite its chemical purity and applicability in the cement and construction industries. This study evaluates the strategic and financial feasibility of commercializing flue gas desulfurization (FGD) gypsum as an unrelated diversification strategy that supports waste reduction, compliance improvement, and alternative revenue generation. The research employs a mixed-method approach combining external analysis, internal analysis, financial viability, and B2B marketing strategy. Findings reveal that the gypsum produced by PT Sumatera Pembangkit meets the technical specifications required by cement producers. The commercialization strategy shows a positive Net Present Value (NPV) and internal rate of return, although it is constrained by regulatory limitations, lack of SNI certification, and infrastructure readiness. The study proposes a phased business model incorporating regulatory enablement, market development, and infrastructure enhancement. The study offers a practical framework for waste utilization in the energy sector and contributes to Indonesia’s circular economy goals by transforming industrial waste into business value.